Robust and repairable bulk polymeric coatings with continuous superhydrophobicity for design control and underwater display. (1st April 2020) - Liu, Maolin; Luo, Yuanfang; Jia, Demin
Abstract: Functionalized polymeric materials with superhydrophobicity are considered as promising candidates for advanced and smart materials. Herein, a bulk superhydrophobic polymeric coating (BSPC) integrating robustness with repairability for design control and underwater display was fabricated based on the combination of covalently cross-linking epoxy acrylate resin (EAR) and hierarchical precipitated silica particle (PSP). By optimizing the ratio of polymer/particle (10: 4), the BSPC exhibited solid mechanical strength while facing various aggressive stress (>200 cycles). Thanks to the continuous superhydrophobicity constructed by hierarchical topography in the polymer skeleton, the BSPC was demonstrated enticing repairable behavior by polish (>40 cycles). More importantly, the regenerative rough structures enabled the BSPC to achieved design control sequentially via the shedding of the surface layer. Simultaneously, based on the underwater light-reflection, the underwater display was successfully realized on the designed BSPC, which may broaden the application fields of superhydrophobic materials. Additionally, the BSPC presented self-cleaning, anti-corrosion (pH in 1/14), anti-boiling (100 °C) and anti-freezing (0 °C) performances. Our findings conceivably propose a feasible strategy to fabricate versatile superhydrophobic polymeric materials with continuous, repairable and designable features for advanced and smart fields. Graphical abstract: Bulk superhydrophobic polymeric coatings with robust and repairable performances for design control and underwater display are fabricated. Image 1 Highlights: A bulk polymeric coating based on epoxy resin and silica particle is proposed. The bulk polymeric coating exhibits a continuous superhydrophobic state. The superhydrophobic coating possesses high mechanical durability. The superhydrophobic coating presents repairable ability via polish treatment. The design control and underwater display are sequentially achieved.